Analysis of Factors Influencing Resistance in Organizations at the Ilir Village Office, Gunungsitoli Sub-district, Gunungsitoli City - Bawamenewi, Arisman; Hulu, Fatolosa; Halawa, Odaligoziduhu; Waruwu, Eliyunus (ProBisnis : Jurnal Manajemen, 2024)
Several problematic phenomena have occurred at the Ilir Village Office, Gunungsitoli Sub-district, Gunungsitoli City, including the emergence of new regulations in managing the organization, which has led to employee resistance, such as changes in office hours. Additionally, the introduction of new innovations or systems in managing and executing office duties and responsibilities, as well as the implementation of new technologies intended to facilitate task execution, have also contributed to resistance. This study aims to identify the factors causing resistance within the organization at the Ilir Village Office, Gunungsitoli Sub-district, Gunungsitoli City, and to determine the efforts made to overcome this resistance. This research is qualitative in nature, with data collection techniques including observation, interviews, and documentation. The informants in this study consist of five employees from the Ilir Village Office, selected using purposive sampling. The results of the study indicate that several factors cause resistance within the organization at the Ilir Village Office. These factors include uncertainty about changes, dissatisfaction with changes, ineffective communication, concerns about job impacts, and worries about changes in compensation. Additionally, the study identifies various efforts that can be made to address this resistance.